Photocatalytic Properties of Co-precipitated Bismuth Cobalt Ferrite - Abi Catur Saputri; Nurdiyantoro Putra Prasetya; Utari Utari; Budi Purnama (Universitas Andalas, 2022)
Bismuth substituted cobalt ferrite nanoparticle is studied for photocatalytic in this paper. Bismuth cobalt ferrite has been synthesized by the coprecipitation method and low-temperature annealing treatment. The characterization results showed that the XRD spectral pattern is consistent with ICDD 221086. The crystallite size of bismuth cobalt ferrite increases with increasing annealing temperature. FTIR results confirm the available metal-oxide at number wave around 570/cm and 475/cm which is the appearance of octahedral and tetrahedral sites owing cobalt ferrite. The photocatalyst test was carried out by varying the catalyst mass and UV irradiation time. The absorption spectrum decreases with increasing catalyst mass. The increase in UV irradiation time causes the formation of more holes (h+) and electrons (e-). So that the hydroxide reaction occurs that produces free radicals. The results of this study indicate that cobalt ferrite-based nanoparticles have potential as photocatalyst materials.